2016
DOI: 10.1158/0008-5472.can-15-0940
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Chromosome Instability Resulted in Colonic Transcriptomic Changes in Metabolic, Proliferation, and Stem Cell Regulators in Sgo1 −/+ Mice

Abstract: Colon cancer is the second most lethal cancer and is predicted to claim 49,700 lives in the U.S this year. Chromosome Instability (CIN) is observed in 80–90% of colon cancers and is thought to contribute to colon cancer progression and recurrence. To investigate the impact of CIN on colon cancer development, we developed shugoshin-1 (Sgo1) haploinsufficient (-/+) mice, an animal model focusing on mitotic error-induced CIN. In this study, we analyzed signature changes in the colonic transcriptome of Sgo1-/+ mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…In particular, the decrease in immune response was an aspect that was not reported previously. Consistent with the pathway analysis, CD8þ T-cells, Nkp46þ NK cells and Nkp1.1þ NK cells isolated from colonic tissues of untreated Sgo1 mice showed significant reduction in g-interferon production compared with control, indicating that Sgo1-CIN mice had partial immune dysfunction [149]. Various immune cell activation markers were downregulated in the lungs of Sgo1 mice [150].…”
Section: Cin Can Enhance Carcinogenesissupporting
confidence: 76%
See 1 more Smart Citation
“…In particular, the decrease in immune response was an aspect that was not reported previously. Consistent with the pathway analysis, CD8þ T-cells, Nkp46þ NK cells and Nkp1.1þ NK cells isolated from colonic tissues of untreated Sgo1 mice showed significant reduction in g-interferon production compared with control, indicating that Sgo1-CIN mice had partial immune dysfunction [149]. Various immune cell activation markers were downregulated in the lungs of Sgo1 mice [150].…”
Section: Cin Can Enhance Carcinogenesissupporting
confidence: 76%
“…Notably, stem cell markers were also misregulated. Collectively, these findings demonstrate that systemic CIN results in transcriptomic changes in metabolism, proliferation, cell fate, and immune responses in the colon, which may foster a microenvironment amenable to cancer development [149]. Lung RNAseq also indicated downregulations in immune function-related pathways, along with misregulations in other oncogenic pathways [150].…”
Section: Cin Can Enhance Carcinogenesismentioning
confidence: 84%
“…As aneuploidy alone also can modify global gene expression [66], can give proteotoxic stress to cells [67,68] and can modulate autophagy [69], genomic instability can have a broad impact on cellular physiology. The findings also suggest that such a CIN-specific gene expression signature and modulation of carcinogenic pathways can be targeted for cancer prevention purposes [64,65].…”
Section: Shugoshin 1 Haploinsufficient Mice (Sgo1-/+) Showed Cohesinomentioning
confidence: 83%
“…Using comparative RNAseq, we demonstrated that these cancer-prone organs (i.e. colon, liver, lung) differentially expressed genes with demonstrated cancer-association [64,65]. The results suggest that CIN alone can modify global gene expression and introduce local proneness (a field effect) to carcinogenesis.…”
Section: Shugoshin 1 Haploinsufficient Mice (Sgo1-/+) Showed Cohesinomentioning
confidence: 88%
“…20, 37 RAG1 −/− mice were obtained from Dr Naveena Janakiram (OUHSC). All mice were maintained in the OUHSC BRC rodent barrier facility.…”
Section: Methodsmentioning
confidence: 99%